Analytical and numerical study of the flow of working fluid in heat pipes - Li, Hui Min (2009)
This work presents the analytical and numerical studies of the flow and heat transfer characteristics in two rotating heat pipes, a conical rotating heat pipe and a rotating heat pipe with a cylindrical evaporator. The simplified momentum equations are solved to predict the film thickness and flow field. A two-dimensional heat conduction model is developed to predict die temperature distribution across the condensate film and along the pipe wall. Moreover, the wall temperature distribution is evaluated numerically by introducing an analogous electrical circuit model and employing an electrical circuit simulation software 'SPICE'. The amount of fluid charge is estimated from the distribution of the condensate film. And the effect of fluid charge on the operational characteristics of the heat pipe is also investigated.